Theories of argument structure - Antonio Fábregas (Borealis: An International Journal of Hispanic Linguistics)
This work discusses the different theories that have attempted to explain the relation between the lexical information provided by a predicate and the syntactic structures that introduce arguments. The focus of the article is in the different sets of assumptions and predictions made by endo-skeletal theories, where lexical items somehow condition the syntactic projection of arguments, and exo-skeletal theories, where lexical items must adapt their meaning to whichever argument structure syntax has defined. In doing so, the article reviews the Theta Criterion, the thematic hierarchy, the notion of linking, the syntactic and semantic decomposition of lexical verbs and the different types of theta role definitions from a formal semantic perspective.